2010
DOI: 10.1177/1753465810376783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulphurous water on human neutrophil elastase release

Abstract: Previous claims concerning the activity of sulphurous water have been based on the patients' subjective sense of wellbeing and on symptomatic (or general) clinical improvements that are not easy to define or quantify exactly. Our findings indicate that, in addition to its known mucolytic and antioxidant activity, sulphurous water also has an anti-elastase activity that may help to control the inflammatory processes of upper and lower airway diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
(35 reference statements)
0
16
0
1
Order By: Relevance
“…Also, it has been observed antioxidant and antiinflammatory properties on in vitro human leucocytes (Braga et al, 2010). Significant beneficial effects on muscle fatigue have been shown from treatments with compounds that promote glutathione synthesis (Ferreira & Reid, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Also, it has been observed antioxidant and antiinflammatory properties on in vitro human leucocytes (Braga et al, 2010). Significant beneficial effects on muscle fatigue have been shown from treatments with compounds that promote glutathione synthesis (Ferreira & Reid, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…One of the working hypothesis was that treatment with salt-bromide-iodine water was able to replace or increase GSH, reducing oxidative stress in lung disorders associated with inflammation, depletion of HS groups and production of ROS [14][15][16]. Recent studies have demonstrated evidences on anti-inflammatory and antioxidative effect of thermal water [1,[17][18][19]. Samples of exhaled breath are suitable medium to study biomarkers of pulmonary inflammation and oxidative stress, which may be sensitive endpoints for identifying biochemical changes in the airways after specific treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of these cures on the recovery of the patients was attributed to the physicochemical properties of the water. Particulary, some studies show that sulphurous thermal water inhalation has mucolitic, antioxidant, and antielastase activity [1] that may help to control airway inflammation at the upper alveolar or lower bronchial level [2,3]. The possible benefit of thermal sulphurous water inhalation could be attributed to the presence of hydrogen sulphide (H 2 S).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its fundamental role in the defensive system of human airways and antioxidant activity, sulfurous water also has an antielastase activity that may help to control the inflammatory processes of upper and lower airways diseases [20]. Gomes et al [19] reported that chloride helps in the cicatrisation and regeneration of tissue and stimulates blood circulation and metabolic functions.…”
Section: Chemical Characteristics Of the Thermal Spring Watermentioning
confidence: 99%